Consumption, credit, and the missing young - Daniel Cooper; Olga Gorbachev; Maria José Luengo-Prado (Federal Reserve Bank of Boston, 2019)
There are more young adults today with either no credit history or insufficient credit history to be scored by one of the major credit bureaus than there were before the Great Recession−a reality that is likely an unintended outcome of the CARD Act of 2009. In regressions that include a rich set of controls, this paper shows that measures of young adults missing from credit bureau data act as a drag on state-level consumption growth. This finding seems to be driven by young individuals from more disadvantaged backgrounds having less access to credit since the act went into effect.
Keywords: E21; D12; 330; consumption; credit